The importance of drafting Arab accounting standards Comparative study in light of international accounting compliance and different environmental factors - لفته منال حسين (Journal of Economics and Administrative Sciences, 2012)
Importance of accounting standards belong to be the instructor and the advisor for accountant in performing his work . For each invironment a group of political, social, economical and cultural factors which distinguish it about other environments . In order to perform its aim in produsing accouting information helps in making decisions on different levels, accounting standards should established in a form that harmonized with the environment that apply in it . Establishing international accounting standards comes with the same direction and then it has put influential with standards some states that have influence on international accounting standards committee. So because of the big changes that happened in the international society and which push toward the globalization, many states has adopted these standards ,and among thes states ,the Arabic states, that have ranged between adopt it perfectly or instruct with it. And regard the international accounting standards a tool for international accounting harmonization who concerns with decreasing the differences in accounting practices and procedures . Hence the research has come to concern with accounting standards and comparing with it between the Arabic states as a developing states and between international standards in the light of international accounting harmonization, and in the same time identify the important charactores that distinguish the Arabic states as a different environment from other states environment .